Effects of Visual Active Deceleration Devices on Controlling Vehicle Speeds in a Long Downhill Tunnel of an Expressway - Fu Wang; Dengjun Gu; Yuanyuan Li; Wei Liu; Guoyun Wang; Naikan Ding (Applied Sciences, 2021)
Because the inside of a road tunnel is a closed strip, the driving environment changes suddenly at the tunnel entrance and exit, which is why accidents occur more frequently in tunnels than elsewhere. Based on visual psychology, reverse-perspective-illusion deceleration lines (RPIDLs) and visual-intervention deceleration devices (VIDDs) were designed to control vehicle speeds near the entrance and in the middle of a tunnel, respectively. Then, to assess the speed-controlling performance of the RPIDLs and VIDDs for vehicles in a long downhill tunnel, laser velocimeters were used to measure the vehicle speeds at different observation points in the tunnel before and after implementing the RPIDLs and VIDDs. The results show that the RPIDLs and VIDDs decreased the average vehicle speed and controlled its dispersion effectively. The 60 m RPIDLs improved the traffic safety in the tunnel without lessening the passing ability therein. The slash-line VIDD had no obvious effect on the maximum vehicle speeds in the middle of the tunnel. Both the 90° fold-line VIDD and the four-yellow–four-white VIDD decreased the maximum vehicle speeds significantly. The 60 m RPIDLs and the 90° fold-line VIDD gave the best deceleration effect on vehicles near the entrance and in the middle of the tunnel, respectively, and controlled the average speed and its dispersion effectively.